Weaving intersectoral networks in the reception of victims of violence in Primary Health Care (Research, Society and Development, 2024)
By producing and reproducing conditions of socioeconomic vulnerability and gender and ethnic-racial inequalities, violence is a challenge for healthcare services, especially primary care, and for public policies. Experiences of violence impact social groups in diverse ways and have proven to be devastating, especially for socially marginalized populations. Thus, the objective of this study is to discuss the importance of acting in an intersectoral network collaboration in supporting victims of violence and the involvement of primary care professionals in prevention and care actions. Focus groups were held with health professionals, community agents, health managers and professionals representing each institution of the intersectoral network, totaling a sample of 36 participants. It is worth highlighting the multiple difficulties in institutionalizing partnerships and joint practices between institutions and agencies that are part of the network of care for people in situations of violence. It is concluded that it is important to qualify professionals who deal with cases of violence in the territory where they work, in addition to improving identification and intervention strategies.